2016
DOI: 10.1063/1.4953397
|View full text |Cite
|
Sign up to set email alerts
|

Low resistivity ZnO-GO electron transport layer based CH3NH3PbI3 solar cells

Abstract: Perovskite based solar cells have demonstrated impressive performances. Controlled environment synthesis and expensive hole transport material impede their potential commercialization. We report ambient air synthesis of hole transport layer free devices using ZnO-GO as electron selective contacts. Solar cells fabricated with hole transport layer free architecture under ambient air conditions with ZnO as electron selective contact achieved an efficiency of 3.02%. We have demonstrated that by incorporating GO in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…The PSC based on this modified ZnO nanorods yields a PCE of 16.1% . Similar results can be obtained by Mg, Go, Sn, In, and Ni doping.…”
Section: The Modification Of Zno Etms For Efficient Pscssupporting
confidence: 81%
“…The PSC based on this modified ZnO nanorods yields a PCE of 16.1% . Similar results can be obtained by Mg, Go, Sn, In, and Ni doping.…”
Section: The Modification Of Zno Etms For Efficient Pscssupporting
confidence: 81%
“…However, the disadvantage of TiO 2 is that high-temperature sintering is often required to obtain the desired nanostructures, which is a barrier to low cost and stretchable device fabrication. ZnO is a practical alternative to TiO 2 to the electron transport layer of solar cells [12,13], lasing [14], detectors [14], LED [15], etc. since it is also an n-type material with a wide direct band gap (E g = 3.37 eV at 300 K).…”
Section: Introductionmentioning
confidence: 99%
“…Pristine graphite depicted a tenacious peak at 26.5° and relocated to 10.8°, as graphite powder was chemically oxidized to form GO through modified Hummers method. Exfoliation of graphite into GO (Ahmed et al 2016;Chao et al 2008) disrupted the basal plane of graphite by adding carbonyl (C=O) and carboxyl (C-OOH) groups located at the edge of graphene nanosheet (Wang et al 2014;Williams & Kamat 2009 Followed by decoration of ZnO NPs on GO nanosheet, the GO nanosheet peak at 10.8° was gone. It was reported that the exfoliation of regular stacks of GO or graphite could diminish or even disappeared the diffraction peak (Chao et al 2008).…”
Section: Results and Discussion Characterization Of Go And Zno-decormentioning
confidence: 99%